Pengaruh Media Baamboozle Terhadap Hasil Belajar Siswa - Riwulang, Nada; Apsarini , Inez Noor; Lutfi Fatma Hilmasari; Sayyidaturrohmah, Sayyidaturrohmah; Sholihah, Ummu; Setyowati , Eni (Papanda, 2026)
This study aims to determine the effect of using learning media through the Baamboozle platform on the mathematics learning outcomes of eighth-grade students at MTsT Al-Atsary. This study is motivated by the low mathematics learning outcomes of students due to the learning methods used by teachers, which are still conventional and student-centered. This study employed a quantitative approach with a quasi-experimental design of the Non-Equivalent Control Group Design type. The research sample consisted of two classes, each comprising 21 students, namely class VIII-A as the experimental group and class VIII-B as the control group, selected using probability sampling techniques. Data were collected using essay tests, and data analysis was conducted using an independent samples t-test. The results showed that the significance value of 0.04 was less than 0.05, indicating that there is a significant effect of the use of Baamboozle media on the mathematics learning outcomes of eighth-grade students at MTsT Al-Atsary, as the use of Baamboozle was found to improve students’ learning outcomes.